Antiviral and immune boosting activities of different medicinal plants against Newcastle disease virus in poultry. Issue 3 (September 2015) - RAZA, A.; MUHAMMAD, F.; BASHIR, S.; ANWAR, M.I.; AWAIS, M.M.; AKHTAR, M.; ASLAM, B.; KHALIQ, T.; NASEER, M.U.
Abstract : The poultry industry is affected by economically important problems such as Newcastle disease (ND). Newcastle disease virus (NDV) belongs to the Paramyxoviridae family and manifests as different strains; lentogenic, mesogenic and velogenic. ND affects the quality of eggs and impairs growth performance of birds. Various efforts have been made to control economic losses due to this disease, including using live and killed vaccines, which do not confer 100% immunity in all cases. Due to mutations within viral strains, NDV can become resistant and difficult to control, and there is a need to search for alternative measures. Medicinal plants are considered as a complementary means to control this virus, especially in developing countries, because they have been implicated in treatments for a variety of infectious and non-infectious diseases. Alkaloids, flavonoids, saponins and tannins found in plants have been regarded as novel antiviral agents. The following paper encompasses the studies related to plants having in vitro antiviral activity against ND such as Momordica balamina, Adansonia digitata, Artemisia annua, Azadirachta indica, Psidium guajava, Moringa oleifera and plants having good in vivo antiviral activity such as Aloe secundiﬂora, Cucumis metuliferus and Anthocleista nobilis as well. It discusses plants with the potential to improve the immunity of infected birds, such as Mangrove halophytes, Nigella sativa, Polysavone, Melissa officinalis, Momordica cochinchinensis, Echinacea purpurea, Withania somnifera and Aspargus Racemosus .